2008
DOI: 10.1177/1046496408315981
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Demographic Differences on Forming Intragroup Relationships

Abstract: Group behavior research suggests that differences among group members cause individuals to interact in ways that may enhance or weaken group performance. Dissimilarities among members may cause the development of negative attitudes about work groups, leading to dysfunctional performance. Network theorists have found that demographic factors influence individuals' tendency to form network ties within their organizations. This article bridges these findings, examining whether work group demographic differences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
1
7
1
Order By: Relevance
“…() find a curvilinear relationship between organizational gender composition and organizational performance, yet they do not investigate the team level. In addition, having a more gender heterogeneous group, that is, a more balanced composition, appears to lower expected negative effects of having such heterogeneity (Valenti and Rockett, ). In order to complement existing work, we thus propose that:Hypothesis The positive association between openness to diversity and performance is moderated by gender diversity in the way that if gender distribution is more balanced, then the effect of openness is stronger.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…() find a curvilinear relationship between organizational gender composition and organizational performance, yet they do not investigate the team level. In addition, having a more gender heterogeneous group, that is, a more balanced composition, appears to lower expected negative effects of having such heterogeneity (Valenti and Rockett, ). In order to complement existing work, we thus propose that:Hypothesis The positive association between openness to diversity and performance is moderated by gender diversity in the way that if gender distribution is more balanced, then the effect of openness is stronger.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…One possible reason why students continue to work with peers outside their formally assigned group is that students do not necessarily join a new group with a "clean slate", as previous experience of working in groups influences students' attitudes towards group work (Chapman, Meuter, Toy, & Wright, 2006;Decuyper et al, 2010;Summers & Volet, 2008). In particular, several recent empirical studies have indeed found that whether (or not) students have already worked together with specific students (Gasevic et al, 2013;Hommes, Arah, et al, 2014) or with students with similar characteristics or social identities, such as academic performance (Mittelmeier et al, 2017), cultural background (Author A, 2014c(Author A, , 2016a, or gender (Bevelander & Page, 2011;Valenti & Rockett, 2008), may influence with whom students develop and maintain relations within and outside their group over time. When students have successfully worked with specific students previously , they do not need to spend a lot of time getting to know each other and building trust if they are enrolled in a new group together in a different module (Hommes, Arah, et al, 2014;Hommes, Van den Bossche, et al, 2014).…”
mentioning
confidence: 99%
“…A LGBTQ faculty member who does not feel comfortable in the workplace may seek fellowship with other LGBTQ and allied individuals. These relations are important because, " .. .interpersonal relations within a group have a spillover effect that affects individual relations outside the group" (Valenti & Rockett, 2008). Faculty members also appreciated their close-knit LGBTQ community.…”
Section: Discussionmentioning
confidence: 99%